Estrategias nutricionales para mejorar la producción y calidad del cultivo de Brócoli (Brassica oleracea) en el Ecuador - España Pereira, Deibby Samanta (2024)
Broccoli, scientifically known as Brassica oleracea, is a cruciferous vegetable prized for its multitude of health benefits, particularly its anti-cancer properties. The use of organic and inorganic nutrition in this crop is related to environmental sustainability and food security. As for inorganic products that are essential if the plant needs them, their excessive use can be toxic, since they can contaminate the soil and water. The present work was carried out with the objective of characterizing effective nutritional strategies to optimize the production and quality of broccoli cultivation in Ecuador and detailing the impact of different sources of organic and inorganic fertilizers on its productivity, as well as establishing the relationship between the extraction of N, P, K and their influence on quality. The results show that the optimal nutritional strategy focuses on the use of mycorrhizal treatments, which stand out in various metrics such as yield, stem length and diameter, as well as leaf length and width. Concluding that the practices that improve the profitability and yield of broccoli cultivation are the use of mycorrhizae, chicken manure fertilizer and rice straw mulch, it being important to adopt these integrated approaches, since this crop takes advantage of organic and inorganic nutrients, optimizing their productivity and being sustainable with the environment. It is recommended to carry out a fertilization plan during the planting period.